Exercise capacity in patients with cystic fibrosis vs. non-cystic fibrosis bronchiectasis - Bar-Yoseph, Ronen (PLoS One, 2019)
BACKGROUND: Bronchiectasis is associated with morbidity, low exercise capacity and poor quality of life. There is a paucity of data on exercise capacity using cardiopulmonary exercise test (CPET) in non-cystic fibrosis (CF) bronchiectasis. Our aim was to compare exercise capacity using CPET in CF and non-CF bronchiectasis patients. METHODS: Cross-sectional retrospective/prospective controlled study assessing CPET using cycle ergometer. Exercise parameters and computed tomography (CT) findings were compared. Results: Hundred two patients with bronchiectasis and 88 controls were evaluated; 49 CF (age 19.7 ± 9.7 y/o, FEV(1)%predicted 70.9 ± 20.5%) and 53 non-CF (18.6 ± 10.6 y/o, FEV(1)%predicted 68.7 ± 21.5%). Peak oxygen uptake (peak [Image: see text] ) was similar and relatively preserved in both groups (CF 1915.5±702.0; non-CF 1740±568; control 2111.0±748.3 mL/min). Breathing limitation was found in the two groups vs. control; low breathing reserve (49% in CF; 43% non-CF; 5% control) and increased [Image: see text] (CF 31.4±4.1, non-CF 31.7±4.1 and control 27.2 ± 2.8). Oxygen pulse was lower in the non-CF; whereas a linear relationship between peak [Image: see text] vs. FEV(1) and vs. FVC was found only for CF. CT score correlated with [Image: see text] and negatively correlated with [Image: see text] and post exercise oxygen saturation (SpO(2)). CONCLUSIONS: CPET parameters may differ between CF and non-CF bronchiectasis. However, normal exercise capacity may be found unrelated to the etiology of the bronchiectasis. Anatomical changes in CT are associated with functional finding of increased [Image: see text] and decreased SpO(2). Larger longitudinal studies including cardiac assessment are needed to better study exercise capacity in different etiologies of non-CF bronchiectasis. TRIAL REGISTRATION: ClinicalTrials.gov, registration number: NCT03147651.